Feto-maternal outcome in grand multipara - Roy, Rajib; Vernekar, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Grand multiparity has been considered as obstetric hazards both to the mother and foetus and thus, viewed with great caution. In present set up grand multiparity is associated with increased likelihood of feto-maternal complications. Methods: The study was conducted to determine the feto-maternal outcome in grand multipara pregnancy. Results: In present study, the prevalence of grand multipara was 0.72% out of 15196 deliveries in the period from September 2010 to august 2012. 79.1% of the grand multipara women belonged to the age group of 31-40 years. A majority of the women were in Para 5. Most of the women had no antenatal care attendance. The highest prevalence of grand multipara women was seen among Muslim community (1.65%). A majority (59.1%) of the women were anemic. Caesarean section rate was 30.0% in our study. Post-partum hemorrhage was the most common complication encountered. 7.0% were macrosomic babies, whereas 8.7% were LBW babies. There were 10 perinatal deaths, birth asphyxia being the most important cause for the perinatal mortality. There were no maternal deaths. Conclusions: Our study demonstrates that, there is increase in antenatal and intra-partum maternal complications like anaemia, hypertensive disorder, preterm labour, increase in the rate of caesarean section, PPH etc., leading to severe maternal morbidity. So, the study concludes that in grand multipara pregnancy, both the woman and the fetus are at a greater risk during pregnancy and labour. This risk can be effectively reduced with good antenatal care and delivery by trained personnel.